The changes of intergovernmental collaboration dynamic in post-disaster destination management: Network analysis. (September 2021) - Wu, Meiling; Gao, Xing; Cao, Mengqiu; Papa, Enrica; Zhu, Xiaoxian
Abstract: Employing network analysis, this study explores the changing dynamics of intergovernmental collaboration throughout the whole process of post-disaster destination management. Jiuzhaigou National Park after the Jiuzhaigou earthquake forms the subject of the case study. Our empirical analysis indicates the following findings: first, intergovernmental collaboration is developed both hierarchically and horizontally at the emergency, intermediate and long-term recovery stages of post-disaster destination management, but it is largely dominated by hierarchical interactions; second, local government increasingly acts as a lubricant role in facilitating the functioning of intergovernmental collaboration during the whole process of post-disaster destination management. These findings contribute to greater insights into the changes of intergovernmental collaboration dynamic in comprehensive post-disaster destination management. This study also provides implications for governments and tourism destinations to improve intergovernmental collaboration for more effective destination management in the context of post-disaster.